Patterns of predator-prey dynamics between gray whales (Eschrichtius robustus) and mysid species in Clayoquot Sound - Burnham, R.; Duffus, D. (J. Cetacean Res. Manage., 2023)
The patterns of foraging intensity of gray whales (Eschrichtius robustus) over a 17-year period (1997–2013) in Clayoquot Sound, Vancouver Island are examined. In this area, epibenthic mysid species are gray whales’ primary prey. The analysis indicates a top-down modification on habitat quality by this apex predator. Intense foraging in one or two summer season contributes to reduced prey resources available in the following summer. Years of heavy predation pressure were followed by at least one year of reduced foraging, probably allowing a reprieve in which the mysids could repopulate. Over the time span several patterns were noted including: boom-bust cycles; extended periods of reduced foraging; an overall declining trend of foraging whales using Clayoquot Sound, followed by a significant prey recovery in 2010. Life history patterns of mysids are discussed in the context of their ability to recover from predation, and how this recovery during a reprieve may buffer the intensity of foraging from the previous year. The continuing ability of mysids to recover from repeated and persistent removal will determine the use of Clayoquot Sound as a gray whale foraging area in the future.